Corporate Tax Policy and the Service Life of Capital Equipment - Malcomson, James M. (Review of Economic Studies, 1981)
Journal Article Corporate Tax Policy and the Service Life of Capital Equipment Get access James M. Malcomson James M. Malcomson University of York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 2, April 1981, Pages 311–316, https://doi.org/10.2307/2296887 Published: 01 April 1981 Article history Received: 01 July 1978 Accepted: 01 September 1980 Published: 01 April 1981